2017
DOI: 10.22606/jaer.2017.24007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opportunities to Learn in Teacher Education on the Development of Teachers’ Professional Knowledge of French as a Foreign Language

Abstract: Abstract. An important goal of teacher education (TE) is to improve pre-service teachers' pedagogical content knowledge (PCK), pedagogical knowledge (PK) and content knowledge (CK). It is not always clear what kind of opportunities to learn (OTL) in TE contribute to pre-service teachers' knowledge development. We compared different cohorts (N = 360) in TE, and studied the effects of OTL (PCK, PK, CK, and practical experiences) on pre-service teachers' PCK, PK and CK (in the domain of French as a foreign langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Pre-service teachers performed better on these items, probably because the conceptual knowledge that is necessary to solve these items is more closely aligned to the learning content provided in TE. Previous studies have shown the impact of courses in TE on pre-service teachers' theoretical knowledge (Evens, Elen, and Depaepe 2017;Blömeke et al 2014). In-service teachers probably did not learn about OI during their own TE, as OI is recently getting more attention in the field of language education (González Humanez and Arias 2009; Herazo Rivera 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-service teachers performed better on these items, probably because the conceptual knowledge that is necessary to solve these items is more closely aligned to the learning content provided in TE. Previous studies have shown the impact of courses in TE on pre-service teachers' theoretical knowledge (Evens, Elen, and Depaepe 2017;Blömeke et al 2014). In-service teachers probably did not learn about OI during their own TE, as OI is recently getting more attention in the field of language education (González Humanez and Arias 2009; Herazo Rivera 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that more courses on PCK lead to more PCK development (i.e. the number of learning opportunities) (Evens, Elen, and Depaepe 2017), and that the inclusion of specific topics in TE (i.e. the content of learning opportunities) also positively impacts PCK (Blömeke et al 2012;Qian and Youngs 2016).…”
Section: Development Of Pckmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative information about the number of credits and/or number of weeks devoted to student internships needs to be complemented with qualitative data on the theoretical courses that are foundational for and related to these practical internships, as well as the organization and content of reflective meetings with the mentors and the supervising team during the internship periods. As argued by other researchers (e.g., Evens et al 2017;Kleickmann et al 2013) both the quantity and the quality of students' practical experiences need to be taken into account in view of their PCK development. Moreover, practical experiences by themselves are insufficient: Critical theoretical reflections on teaching experiences can seriously enhance students' understanding of effective teaching interventions in the domain of (early) mathematics (Strawhecker 2005).…”
Section: Preservice Preschool Teachers' Pck and Otl During Teacher Trainingmentioning
confidence: 99%
“…Whereas teacher education aims to provide the basis for professional pedagogical practices and attitudes (Watzke, 2007), studies investigating the impact of teacher education on FL student teachers displayed varying results (e.g. Evens, Elen & Depaepe, 2017;Kleinhenz et al, 2007;König et al, 2016). Some studies found evidence for FL teacher education influencing student teachers (see Borg, 2011;Busch, 2010), whereas others reported no change during teacher education or no long-term effect of teacher education (see Graus & Coppen, 2016;Peacock, 2001;Phipps, 2007;Pickering, 2005;Urmston, 2003).…”
Section: Introductionmentioning
confidence: 99%